Analisis Pengaruh Investasi Singapura terhadap Pertumbuhan Ekonomi Indonesia - Meiriza, Mica Siar; Dwi, Vingky; Rezeki, Mentari; Safira, Vivi; 'Afifah, Zulfa; Manurung, Tasya (Ikatan Da'i Indonesia, 2024)
Singapore's foreign investment has an important role in economics development in Indonesia's. In the era of increasing globalization and economic integration, the flow of foreign investment has become a key factor in improving the welfare of the Indonesian people. Singapore, as Indonesia's largest trading partner, has made significant investments in various sectors in Indonesia, with quite a large impact on the economy and society. This research uses a qualitative approach to analyze the impact of Singapore investment on Indonesia's economic growth. The research results show that foreign investment brings capital, technology and management that increase the productivity and competitiveness of Indonesian industry. This investment plays a role in developing infrastructure that supports long-term economic growth. This research has global relevance because Singapore is one of the largest financial and trade centers in the world, and Indonesian can be a role model for other countries. It is hoped that the results of this research will provide valuable insights for the development of economic policy in Indonesia and strengthen economic relations between Indonesia and Singapore.